Comparison of short‐term outcomes of robotic‐assisted and conventional laparoscopic surgery for rectal cancer: A propensity score‐matched analysis. Issue 4 (12th May 2022) - Yamanashi, Takahiro; Miura, Hirohisa; Tanaka, Toshimichi; Watanabe, Akiko; Goto, Takuya; Yokoi, Keigo; Kojo, Ken; Niihara, Masahiro; Hosoda, Kei; Kaizu, Takashi; Yamashita, Keishi; Sato, Takeo; et al.
Abstract: Introduction: The advantages of robotic‐assisted laparoscopic surgery (RALS) for rectal cancer remain controversial. This study clarified and compared the short‐term outcomes of RALS for rectal cancer with those of conventional laparoscopic surgery (CLS). Methods: The records of 303 consecutive patients who underwent RALS or CLS for rectal adenocarcinoma between November 2016 and November 2021 were analyzed using propensity score‐matched analysis. After matching, 188 patients were enrolled in our study to compare short‐term outcomes, such as operative results, postoperative complications, and pathological findings, in each group. Results: After matching, baseline characteristics were comparable between groups. Although operative time in the RALS group was significantly longer than in the CLS group ( p  < 0.0001), the conversion rate to open laparotomy and the postoperative complication rate in the RALS group were significantly lower than in the CLS group ( p  = 0.0240 and p  = 0.0109, respectively). Blood loss was comparable between groups. In the RALS group, postoperative hospital stay and days to soft diet were significantly shorter than those in the CLS group ( p  = 0.0464 and p  < 0.0001, respectively). No postoperative mortality was observed in either group and significant differences were observed in resection margins and number of lymph nodes harvested. Conclusion: Robotic‐assisted laparoscopic surgery for rectal cancer was safe, technically feasible, and had acceptable short‐term outcomes. Further studies are required to validate long‐term oncological outcomes.